Osaka modern the city in the Japanese imaginary - Cronin, Michael P. (Harvard East Asian monographs, 2017)
"Examines the relationship between local and national orders of space, language, daily practice, etc. in literature, cinema, and other popular culture of the city of Osaka produced during the transwar era, from the 1920s through the 1950s"--